HCV INDUCED COMPLICATIONS DURING PREGNANCY AND NEONATAL RISKS - NAWAZ , R; NAZ , Z; IQBAL , B; AHMAD , M; RAZA , MS; RAZA , M; WASEEM , M; AHAD , A; SHAHZADI , K (Biological and Clinical Sciences Research Journal, 2024)
Hepatitis C Virus (HCV) is a frequent health concern that causes pregnancy-related disorders such as intrahepatic cholestasis, preeclampsia, preterm delivery, gestational diabetes mellitus, and increased bile acid concentration in pregnant women. The cause of premature delivery in HCV-infected pregnant women is unknown, however alcohol is a risk factor. Many variables contribute to a higher likelihood of HCV transfer from mother to newborn, including a high viral load along with HIV co-infection, protracted membrane breach, and vaginal laceration. Neonatal problems caused by HCV include low birth weight due to a maternal placental inflammatory lesion, fetal distress, in which the infant suffers from oxygen shortage and preterm birth. Antiviral treatment for HCV pregnant women is contradictory. Ribavirin and interferon are not utilized as treatments for HCV in pregnant women due to the potential for teratogenicity and psychological adverse effects. In addition to causing pregnancy-related complications, HCV may have several harmful impacts on the fetus.